Assessing future climate change with a weather generator: A case study in Bali, Indonesia - Ayu Puspitasari Sylvatera; Wu Chen-Fa (BIO Web of Conferences)
Bali is one of the largest rice granaries in Indonesia, with 668,612 tons produced in 2023. Hence, agriculture is one of the crucial sectors in Bali. Climate change can affect the agriculture sector in many ways. It can cause the conditions to be better or worse for growing plants in distinct areas. Forecasting future climate change is needed to understand extreme conditions in the long term. Thus, climate change scenarios are required to evaluate agriculture impacts. We use the MarkSim weather generator with 17 models under different scenarios and collected rainfall and temperature data from 2026-2091. The MarkSim weather generator can be utilized to predict future climate change in Bali, Indonesia. Rainfall in the coming years is expected to fluctuate annually, yet it will remain within a relatively stable range of 2066 to 2170 mm. Both maximum temperature (Tmax) and minimum temperature (Tmin) are projected to continue to rise, with increases of up to 2 °C. This study offers valuable insights into climate change impact models on agriculture, which is helpful for farmers, researchers, planners, and decision-makers.